Optimization of braided reinforced composite rods - Pereira, Cristiana Gonilho (2020)
This work described the deveÌopment of braided reinforced composite rods for concrete reinforcement. The research study aims to analyse the influence of braided fabrics geometry on the core reinforced braided fabrics mechanical behaviour. Moreover, this study intends to identify the influence of different fiber types used as core reinforcement and of testing conditions on the mechanical properties of braided fabric composite rods.